Analysis of Decision Making on Wastewater Use Technology in the Universitas Pertamina Area - Khansa, Pavita; Sofiyah, Evi Siti; Suryawan, I Wayan Koko (Universitas Diponegoro, 2023)
Wastewater available through the sewerage system can be reused as a daily need. With a sewer system, the Universitas Pertamina Area can utilize water according to Government Regulation of the Republic of Indonesia Number 82 of 2001 Class 4. Reuse of wastewater within this scope can improve sustainable development goals. This study aims to analyze the decision-making of sewerage water treatment so that it can be reused according to the class 4 quality standard. The first alternative consists of a collection tank, bar screen, pre-sedimentation, rapid sand filter (RSF), and disinfection. The second alternative consists of a collection tank, bar screen, horizontal roughing filter (HRF), RSF, and disinfection. The two alternatives provided have met the required quality standards. However, the area of land required in alternative one is too large compared to the second alternative. This causes the second alternative to be more appropriate to be applied in the Universitas Pertamina Area. Analysis of decision-making on the use of RSF media is carried out using the Analytical Hierarchy Process (AHP). The alternative media for RSF are sand, granular active carbon (GAC), and zeolite. The criteria for BOD removal, total coliform removal, cost, headloss, and replacement period of the most appropriate zeolite media for use in the RSF unit process.